THE POSSIBLE INFLUENCES OF GRECO-ROMAN ASSO-CIATIONS ON THE CORINTHIAN EKKLĒSIA: AN EXAMI-NATION OF 1 COR 11:17–34 - Mpereh, Samuel V. (Ghana bulletin of theology, 2016)
There have been various approaches to unearthing Paul’s intention in 1 Cor 11:17-34. This study attempts to verify the possible influences Paul’s instructions might have had on the members of the Corinthian ekklēsia. The ritual structure of the Corinthian deipnon offers an inimitable opportunity for Paul to try to end the schismata in the ekklēsia. It is plausible that the Corinthian deipnon might be the type of meal akin to the voluntary associations in particular and in the Greco-Roman milieu in general. This is evidenced by certain features of the Greco-Roman meal practices, which were similar to the Corinthian deipnon. The ritual Paul is helping to create shaped the community through action. The application of ritual studies to the passage under review has the following advantages: It is void of mirror reading and situates the passage in its ritual setting.